INSILCO STUDY OF MACITENTAN AGAINST DIFFERENT MICROBIAL TARGET AS POSSIBLE ANTIBACTERIAL AGENT - Sadeq Jaafer Al-Tameemi (Web of Journals Publishing, 2024)
Background: Many of non-antibiotics drug such as anesthetics, diuretics, anticoagulants, antihypertensive and mucolytic drugs, have shown some antimicrobial activity. Antimicrobial resistance is a global human and economic burden that is increasing annually. No new antimicrobial is effective against microbial resistance however there is increase the development of bacterial drug resistant. For that its important to find a drug to limit or overcome the bacterial resistant. Our object to find out the effect of Macitentan against different microbial target associated with drug resistant Method: The molecular docking of Macitentan as possible antibacterial drug against NMD 1, Als3 FmlD, Com E, and HSK shows height affinity. The binding energy was 7.28, 5.52, 4.38, 6.60, and 5.64 respectively. Result: the drug shows good binding activity against NDM-1 binding energy (-7.28 kcal/mol), Com E (-6.60 kcal/mol) , moderate activity for Als3 (-5.52 kcal/mol) , FmlD (-4.38 kcal/mol) and HSK (-5.64 kcal/mol) Conclusion Macitentan may be a useful resource for the creation of novel anti-infective substances. Docking experiments were conducted on two significant targets, purpose elucidating a putative mechanism of action for the molecule that was shown to be the most active.
Keywords: Anti-Bacterial Agents; Antihypertensive Agents; Molecular Docking Simulation; macitentan.